2021
DOI: 10.21608/ejchem.2021.77134.3780
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination chemistry and cyclic voltammetry exploration of Cu(II), Co(II), Ni(II) and Zn(II) complexes of novel (E)-3,4-dichloro-N-(2-(1-(pyridin-2-yl)ethylidene)hydrazine-1-carbonothioyl) benzamide ligand

Abstract: The Coordination chemistry and cyclic voltammetry exploration of Cu(II), Co(II), Ni(II) and Zn(II) complexes of novel (E)-3,4-dichloro-N-(2-(1-(pyridin-2-yl)ethylidene)hydrazine-1-carbonothioyl) benzamide ligand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…We notice that the redox potential of Co(IV)/Co(II) is recognized to be higher than HSO 5 − /SO 4 2− (>1.88 V vs 1.82 V), [26] however, the overall potential of PMS for oxidizing magnetization tests reveal that the single Co atoms in Co SA -BNC possess a high spin state (Figure S35c, Supporting Information). Upon simulating the rearrangement of d-electrons with a square planar crystal field, [27] we found that the two most easily lost electrons are located in different energy levels (Figure S35d, Supporting Information), making them capable of losing in a suc-cessive way. Due to O-H bond cleavage can take place when the two-electron transfer occurs between Co-O in CoB 1 N 3 /PMS, free radicals are not likely to be produced even when Co(III) intermediates exist.…”
Section: Resultsmentioning
confidence: 99%
“…We notice that the redox potential of Co(IV)/Co(II) is recognized to be higher than HSO 5 − /SO 4 2− (>1.88 V vs 1.82 V), [26] however, the overall potential of PMS for oxidizing magnetization tests reveal that the single Co atoms in Co SA -BNC possess a high spin state (Figure S35c, Supporting Information). Upon simulating the rearrangement of d-electrons with a square planar crystal field, [27] we found that the two most easily lost electrons are located in different energy levels (Figure S35d, Supporting Information), making them capable of losing in a suc-cessive way. Due to O-H bond cleavage can take place when the two-electron transfer occurs between Co-O in CoB 1 N 3 /PMS, free radicals are not likely to be produced even when Co(III) intermediates exist.…”
Section: Resultsmentioning
confidence: 99%
“…All obtained coordination compounds have new-formed peaks in the range of 3600-3400 cm −1 which can be attributed to the ν(OH). In the spectrum of pure ligand, the strong peak at 1681 cm −1 is presented, which corresponds to the ν(C=O) presence [27]…”
Section: Thermogravimetric Analysis (Tga) Analysismentioning
confidence: 99%
“…All obtained coordination compounds have new-formed peaks in the range of 3600-3400 cm −1 which can be attributed to the ν(OH). In the spectrum of pure ligand, the strong peak at 1681 cm −1 is presented, which corresponds to the ν(C=O) presence [27]. In the case of [Co(L)Cl2], [Ni(L)Cl2(H2O)], [Cu(L)Cl2(H2O)] and [Zn(L)Cl2] this peak is very weak or completely absent, indicating the movement of the hydrogen atom to the nearest donor atom, which leads to the formation of the C-OH group.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…Its importance is because the rapid oxidationreduction information of the metal complexes can be provided everywhere in the used potential range. 43 Using the C.V. technique, the redox behavior of both divalent cobalt and manganese was accomplished on a freshly glassy carbon working electrode immersed in 0.1 M of KCl as supporting electrolyte, applying a scan rate of 0.1 V/s at 298 K. A solution of the metal salt was poured slowly until the final concentration of each metal reached 1.61 Â 10 À3 M. The voltammogram curves showed that the cobalt ions are electroactive and demonstrated one reduction wave corresponding to Co(II) + 2e!Co 0 , Ep,c = À0.882 V and the other peak at À0.16 V represents the oxidation wave, corresponding to Co 0 !Co(II). While the Mn(II) ions exhibited two oxidation peaks corresponding to Mn 0 !Mn(I) + e and Mn(I)!Mn(II) + e, as well as two reduction peaks due to Mn(II) + e!Mn(I) and Mn(I) + e!Mn 0 .…”
Section: Cyclic Voltammetric Studymentioning
confidence: 99%